Foxp3 Expression in Liver Correlates with the Degree but Not the Cause of Inflammation - Matthaios Speletas; Nikoletta Argentou; Georgios Germanidis; Themistoclis Vasiliadis; Konstantinos Mantzoukis; Kalliopi Patsiaoura; Pavlos Nikolaidis; Vaios Karanikas; Konstantinos Ritis; Anastasios E. Germenis (Hindawi Limited, 2011)
Patients with chronic viral hepatitis display increased expression of Foxp3 in liver, suggesting that Tregs expansion contributes to persistent infection. The purpose of this study was to elucidate whether the expression of Foxp3 relates not to the viral infection but to the resulting liver inflammation. Liver biopsies obtained from 69 individuals (26 chronic HBV hepatitis, 14 chronic HCV hepatitis, 11 nonalcoholic fatty liver disease, 8 autoimmune diseases, 2 methotrexate-related toxicity, and 8 controls) were examined, by qRT-PCR, for the mRNA expression of Foxp3, IL-10, TGF-β1, Fas, FasL, TRAIL, caspase-3, TNF-α, IFN-γ, and IL-1β. Significant increase of Foxp3 was observed in all disease groups compared to controls, which was positively correlated with the intensity of inflammation. The expression of the apoptosis mediators Fas, FasL, and TRAIL, but not of IL-10 and TGF-β1, was also significantly elevated. Our findings indicate that, independently of the initial inducer, liver inflammation is correlated with elevated expression of apoptosis mediators and is followed by local Treg accumulation. Further research towards the elucidation of the underlying casual relationships is required, in order to clarify whether our results signify the existence of a uniform Treg-mediated regulatory mechanism of apoptosis-induced inflammation.